Evaluation of the International Finance Corporation's Global Trade Finance Program, 2006-12 - Independent Evaluation Group (Washington, DC: World Bank, 2013)
The International Finance Corporation (IFC) introduced the Global Trade Finance Program (GTFP) in 2005 is to 'support the extension of trade finance to underserved clients globally.' The program has since expanded rapidly, and its authorized exposure ceiling was increased in three stages from $500 million in 2005 to $5 billion in 2012. In FY12, the GTFP accounted for 39 percent of total IFC commitments, 53 percent of its commitments in Sub Saharan Africa, and 48 percent of its commitments in Latin America and the Caribbean. The Independent Evaluation Group (IEG) recommends that IFC (i) continue to strengthen the GTFP's focus in areas where additionally is high and increase the share of the program in high-risk markets and where the supply of trade finance and alternate risk-mitigation instruments are less available; (ii) adopt additional methods of reporting volume that can reflect the distinct nature of trade finance guarantees; (iii) refine the means by which GTFP profitability is monitored and reported; (iv) review the costs and benefits of the current monitoring and evaluation framework; (v) ensure that a transparent process is in place to govern cases of covenant breach; and (vi) enhance the program's ability to meet the demand for coverage of longer-term trade finance tenors.